Indigiqueerness : a conversation about storytelling - Whitehead, Joshua (Writer); Abdou, Angie, 1969- (AU Press, 2023)
"Evolving from a conversation between Joshua Whitehead and Angie Abdou, Indigiqueerness is part dialogue, part collage, and part memoir. Beginning with memories of his childhood poetry and prose and travelling through the library of his life, Whitehead contemplates the role of theory, Indigenous language, queerness, and fantastical worlds in all his artistic pursuits. This volume is imbued with Whitehead's energy and celebrates Indigenous writers and creators who defy expectations and transcend genres."--